2016
DOI: 10.1097/scs.0000000000002403
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes Between the Level of Velopharyngeal Closure and the Cervical Spine

Abstract: The primary focus of this study was to assess age related changes in the vertical distance of the estimated level of velopharyngeal closure in relation to a prominent landmark of the cervical spine: the anterior tubercle of cervical vertebrae one (C1). Midsagittal anatomical magnetic resonance images (MRI) were examined across 51 participants with normal head and neck anatomy between 4 and 17 years of age. Results indicate that age is a strong predictor (p = 0.002) of the vertical distance between the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…Changes in velar shape are likely due to growth of the velum as children mature. Previous studies have reported that growth led to increased velar length and velar thickness 2223. These anatomical changes likely result in the presence of certain velar shapes in adults.…”
Section: Discussionmentioning
confidence: 87%
“…Changes in velar shape are likely due to growth of the velum as children mature. Previous studies have reported that growth led to increased velar length and velar thickness 2223. These anatomical changes likely result in the presence of certain velar shapes in adults.…”
Section: Discussionmentioning
confidence: 87%
“…), or identifying the level of proper velopharyngeal closure correction in patients with cleft palate (Mason et al. ). Similarly, orthodontists use cervical vertebral body morphological stages to identify the biological age of a patient to determine appropriate treatment (Bench, ; Altan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have emphasized the value of using presurgical anatomy that is sex and race specific to guide proper surgical treatment in cleft palate surgeries (Chung & Kau, 1985;Chung, Runck, Bilben, & Kau, 1986;Inouye, Pelland, Lin, Borowitz, & Blemker, 2015;Mason, Perry, Riski, & Fang, 2016;Mason, Riski, & Perry, 2018;. However, our understanding of the timing in which sex effects are evident is limited to young child and adult age groups and is not reflective of data across the age span.…”
mentioning
confidence: 99%